2020
DOI: 10.1523/eneuro.0276-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Accumbens Cholinergic Interneurons Mediate Cue-Induced Nicotine Seeking and Associated Glutamatergic Plasticity

Abstract: Nicotine, the primary addictive substance in tobacco, is widely abused. Relapse to cues associated with nicotine results in increased glutamate release within nucleus accumbens core (NAcore), modifying synaptic plasticity of medium spiny neurons (MSNs) which contributes to reinstatement of nicotine seeking. However, the role of cholinergic interneurons (ChIs) within the NAcore in mediating these neurobehavioral processes is unknown. ChIs represent less than 1% of the accumbens neuronal population and are activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Estradiol treatment decreased striatal dopamine D2 receptor binding, and variations in dopamine levels and binding are seen in different phases of the estrous cycle in rats ( Bazzett and Becker, 1994 ; Al Sweidi et al, 2013 ). Still, there appears to be no estrous cycle dependent changes or sex differences when monitoring nicotine self-administration and reinstatement of nicotine-seeking ( Feltenstein et al, 2012 ; Leyrer-Jackson et al, 2021 ). In vivo spontaneous activity of dopamine neurons, as well as ex vivo intrinsic and synaptic properties, have also been reported to be similar in male and female rats ( Melis et al, 2013 ), even though there appears to be a sex difference with regards to tonic 2-AG signaling on to dopaminergic neurons ( Melis et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol treatment decreased striatal dopamine D2 receptor binding, and variations in dopamine levels and binding are seen in different phases of the estrous cycle in rats ( Bazzett and Becker, 1994 ; Al Sweidi et al, 2013 ). Still, there appears to be no estrous cycle dependent changes or sex differences when monitoring nicotine self-administration and reinstatement of nicotine-seeking ( Feltenstein et al, 2012 ; Leyrer-Jackson et al, 2021 ). In vivo spontaneous activity of dopamine neurons, as well as ex vivo intrinsic and synaptic properties, have also been reported to be similar in male and female rats ( Melis et al, 2013 ), even though there appears to be a sex difference with regards to tonic 2-AG signaling on to dopaminergic neurons ( Melis et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The chemogenetic technique has been widely used to understand the neurobiology of addiction, especially the role of selective neuronal populations in the NAc in nicotine and alcohol addiction (Leyrer‐Jackson et al., 2021; Strong et al., 2020). By introducing G protein‐coupled inhibitory (Gi) or excitatory (Gq) DREADD receptors into CINs through cre‐dependent viral vectors, we were able to control the activity of CINs in response to CNO (Ferguson et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Our prior studies have examined plasticity during reinstatement of nicotine seeking in male rats, which is a protracted time point from nicotine self-administration ( Gipson et al, 2013b ; Namba et al, 2020 ; Leyrer-Jackson et al, 2021 ). In our first paper examining NAcore plasticity following nicotine self-administration, we found that initiated nicotine seeking in a cue-induced reinstatement model potentiated NAcore MSNs, which then collapsed within 45 min (similar to when active lever pressing declined; Gipson et al, 2013a ).…”
Section: Discussionmentioning
confidence: 99%